Concentrations of polybrominated diphenyl ethers in breast milk correlated to maternal age, education level, and occupational exposure - Chao, H. Albert; Chen, Solomon Chih-Cheng; Chang, Ching-Mine; Koh, Teck-Wai; Chang-Chien, Gou-Ping; Ouyang, Eileen; Lin, Show-Lian; Shy, Cherng-Gueih; Chen, Fu-An; Chao, How-Ran (Journal of hazardous materials, 2010)
The aim of the present study is to determine whether levels of polybrominated diphenyl ethers in breast milk in the general population are associated with demographic parameters, socioeconomic status, lifestyle factors, and occupational exposure. Forty-six participants are randomly selected from healthy women recruited between April 2007 and April 2008 from local hospitals in southern Taiwan. Thirty PBDE isomers in breast milk are analyzed using a gas chromatograph with a high resolution mass spectrometer. The mean ± standard deviation of ∑PBDEs in breast milk is 3.59 ± 1.07 ng/g lipid. Our current value of ∑PBDEs in breast milk is 0.7-fold lower compared to the past value in our previous study between 2000 and 2001. Higher levels of ∑PBDEs might be significantly associated with older maternal age and maternal age of the present study is between 22 and 42 years old. Levels of ∑PBDEs and certain PBDEs in breast milk are not correlated with maternal pre-pregnant BMI (Body mass index), parity, and lipid contents of breast milk. The ∑PBDEs level in breast milk is lower in more educated women after controlling for age and pre-pregnancy BMI in our subjects. The main factors associated with ∑PBDEs in breast milk are age and education level among the binary variables of demographic, socioeconomic, and lifestyle characteristics in this report. The exploratory relationships are found between PBDEs in breast milk and age, education level, or occupational exposure due to small sampling size.